Opioids, Race, Context, and Journeys to Crime: Analyzing Black–White Differences in Travel Associated With Opioid Possession Offenses - Donnelly, Ellen A. (Criminal justice and behavior, 2021)
Journeys to crime, or distances traveled from residences to places of alleged crimes, describe how people enter into the criminal justice system. Race, as an ascribed characteristic of individuals and a determinant of community conditions, introduces disparities in journeys to crime. Use of opioids among nonurban, White populations and changing law enforcement responses prompt inquiry into how race affects journeys to crime associated with opioid possession. This study evaluates Black–White differences in travel among persons arrested for opioid possession in Delaware. It applies race and rationality theory to assess the effects of race and racialized context on travel patterns. Multilevel models reveal travel to possess opioids is greater for White relative to Black Delawareans. Community conditions such as marijuana possession arrest rates and concentrated disadvantage have varying impacts on travel from various geographic areas. Racial–spatial differences in travel show persistent disparities in drug law enforcement amid efforts to curb opioid misuse.